2017
DOI: 10.1139/cjc-2016-0413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel α-aminoecdysteroids via regio- and stereoselective oximation/hydrogenation of 20-hydroxyecdysone derivatives

Abstract: Oximation of 20-hydroxyecdysone oxo derivatives proceeds regio- and stereoselectively and provides (E)-configured oximes in quantitative yields. The Ni–Ra-catalyzed hydrogenation of the oximes affords novel α-aminoecdysteroids with the unchanged 14α-hydroxy-7-en-6-on native chromophore of ecdysteroids. The structures of synthesized compounds were confirmed by the means of homo- and heteronuclear one-dimensional and two-dimensional 1H and 13C NMR spectroscopy and X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Our HMBC measurement (see Figure S5, cross‐peaks H‐9/C‐11 and H‐17/C‐16) revealed that the assignment of the CH 2 signals in positions 11 and 16 is in fact the opposite as compared to that published . Furthermore, based on the edited‐HSQC spectrum (Figure S4), we achieved full assignment of the diastereotopic methylene hydrogen atoms as well.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our HMBC measurement (see Figure S5, cross‐peaks H‐9/C‐11 and H‐17/C‐16) revealed that the assignment of the CH 2 signals in positions 11 and 16 is in fact the opposite as compared to that published . Furthermore, based on the edited‐HSQC spectrum (Figure S4), we achieved full assignment of the diastereotopic methylene hydrogen atoms as well.…”
Section: Resultssupporting
confidence: 90%
“…Savchenko and coworkers most recently reported the 1 H and 13 C NMR data of 20‐oxime derivative of posterone 2,3‐acetonide ( 2 ), and on the basis of its X‐ray single crystal investigation, they proved the ( E )‐configuration of the oxime moiety . As in the 1 H and 13 C NMR spectra of this compound only one set of signals appeared, the measured diamagnetic change of δC‐20 (Δδ 51 ppm) supported the C═O → C═NOH conversion, but in the absence of exact data of Δδ syn ‐ anti parameters for the C‐21 signal, the unambiguous identification of the E / Z isomerism was not possible.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations